2013
DOI: 10.1063/1.4820262
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the resupply, diffusion, and evaporation of cesium on the surface of controlled porosity dispenser photocathodes

Abstract: A controlled porosity dispenser (CPD) photocathode is currently being explored and developed to replace the Cs during operation and increase photocathode lifetime. Experimental results from cesium (Cs) emission of a sintered-wire tungsten CPD are presented and are used to inform a theoretical model of Cs resupply, diffusion, and evaporation on the surface of the photocathode. The evaporation of Cs from a tungsten surface is modeled using an effective one-dimensional potential well representation of the binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…where σ is the flux of cesium atoms to the surface and ν is the rate of evaporation from the surface at the monolayer coverage (θ = 1). Analytical deduction of the rate of evaporation is more complex [19], and so we use an empirical formula for the Flow chart summarizing the analytical approach followed for determining total cooling flux from a porous tungsten surface through which cesium is transpired.…”
Section: Experimental Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…where σ is the flux of cesium atoms to the surface and ν is the rate of evaporation from the surface at the monolayer coverage (θ = 1). Analytical deduction of the rate of evaporation is more complex [19], and so we use an empirical formula for the Flow chart summarizing the analytical approach followed for determining total cooling flux from a porous tungsten surface through which cesium is transpired.…”
Section: Experimental Validationmentioning
confidence: 99%
“…In this study, we perform a theoretical analysis of the nearsurface effects for the case of the liquid cesium injected into the air plasma through a porous tungsten surface at the leading edge, which will be referred to as the emitter surface. Cesium injection and diffusion through porous tungsten surface was briefly discussed in references [18,19], where authors studied cesium-based dispenser photocathodes. The mechanism of the cesium injection in hypersonic flight conditions and experimental proof of the proposed ETC concept are the subject of active research within the framework of the project, which will be reported in a future study.…”
Section: Introductionmentioning
confidence: 99%